Avaliação da frequência de transtorno de déficit de atenção e hiperatividade em pacientes submetidos à cirurgia bariátrica e sua relação com a evolução ponderal no período pós-operatório - Marchesi, Doglas Gobbi (2014)
Introduction: Bariatric surgery shows effective and consecrated results in combating the obesity pandemic. However, few studies evaluate the prognostic factors in the success of the surgical treatment of obesity. Recently, studies described that the Attention Deficit and Hyperactivity Disorder (ADHD) is directly related to obesity and a greater difficulty in losing weight with nonsurgery therapy. This study intends to start analyzing possible negative effects of ADHD on the success of bariatric surgery. Methods: Forty patients that have undergone bariatric surgery and with minimal regular postoperative follow-up of one year were evaluated. All underwent the recommended questionnaire in the fourth edition of the Diagnostic and Statistical Manual (DSM-IV) of the American Psychiatric Association for ADHD and analyzed the postoperative data. Results: Thirteen (38%) patients had a positive questionnaire for ADHD. The patient with ADHD had higher BMI than patients without the disorder, keeping the difference in all stages of postoperative follow-up. No statistically significant difference in the success of surgery (p = 0.505) and in the reduction in BMI (p = 0.671) was found, after a year of the procedure. Conclusion: Patients with ADHD have higher BMI, however, the presence of ADHD has no influence on the success of bariatric surgery and reduction in BMI. Despite the findings, other studies evaluating other data such as postoperative complications, longer follow-up, improvement in comorbidities, among others, are necessary to define the actual influence of ADHD postoperative bariatric surgery.